Pengaruh Kualitas Pelayanan Dan Store Atmosphere Terhadap Minat Berkunjung Kembali Pada Toko Retail Modern Guardian Di Kota Bandung - Ghina Fitria Fitria; Siti Herawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Retail Guardian, as one of the stores whose core business is in the health and beauty sector, is indicated to be experiencing a decline in sales with the main problem being low interest in returning visits. This is indicated by its position as the top brand in 2022-2023 experiencing a decline while its competitors in the same industry experience an increase. The aim of this research is to analyze the influence of service quality and store atmosphere on interest in returning to visit. This research uses a quantitative approach with data collection techniques through questionnaires using a Likert scale and has been declared valid and reliable. The questionnaire was distributed to 93 respondents who were determined using a probability sampling technique using the purposive sampling method. There are three hypotheses derived from the research objectives which are tested using multiple regression, which as one of the conditions has passed the classical assumption test. This research showed that of the three hypotheses, 2 were proven to be influential and 1 hypothesis had no effect.